MENDESAIN VIDEO YANG MENARIK DALAM PEMBELAJARAN MEMBACA AL-QURAN DI ERA NEW NORMAL - Rikarno, Riki; Maimori, Romi; Yuliani, Tri (UNIVERSITAS INDO GLOBAL MANDIRI, 2021)
Many learning videos have been created, both by educators and companies engaged in education, of the many learning videos spread through social media for learning videos to read the Qur'an, it can be said that the percentage is very small. For this reason, the author who is in an Islamic Education institution, has the desire to describe the design of an interesting learning video for reading the Qur'an so that later it can be disseminated through social media, later teachers at schools or in Al-Quran Education places can make your own learning videos using simple tools for effective learning achievement in learning in the current new normal era. Video learning to read the Qur'an is a media that presents audio and visuals that contain good learning messages that contain concepts, principles, procedures, knowledge application theories to help understanding a learning material to read the Qur'an. Video is a visible and heard learning material (audio visual) that can be used to convey messages / subject matter. Learning videos can be classified into audio visual aids (AVA) media types or media that can be seen and heard. Usually this media is stored in the form of data. For an educator can use learning media to read the Koran so that students are more enthusiastic in following the lessons delivered so that learning motivation will increase. This learning video can not only be produced for reading the Koran but for all materials it can be made according to the shape of the material.